Effects of School Environment on the Proficient Use of French Language by Secondary Schools in Owo Local Government, Ondo State, Nigeria - Love O., Saba (International Journal For Research In Educational Studies, 2016)
The importance of school environment on student performance in respect of language acquisition cannot be overemphasised. The learning environment in which students learn such as classrooms, libraries, technical workshops, laboratories, playgrounds, conveniences, sanitation maintenance, culture, aesthetics among others, are variables that affect students‟ learning and academic performance (Duruji et al; 2014). School environment has great impact in the quality of teaching that students receive and the extent of attention they pay to lessons in schools. This implies that schools that fail to provide the necessary learning facilities and create a conducive atmosphere for teaching and learning may hardly put in the best in their students especially when it comes to acquiring a foreign language such as French where it is in position of “Langue étrangère” where the most important part is communicative aspect of it. This scenario has been among the reasons for poor proficient use of French Language among the secondary school students in Owo Local Government Area(OLGA), Ondo State, Nigeria. The main thrust of this paper is to investigate the effects of school environment on the proficient use of French Language (FL) “Langue étrangère” (Le) in the study area. Three research questions and three hypothesis guided the study. A total number of one hundred students from ten schools and twenty French teachers of secondary schools in OLGA attempted a 15 questionnaire- test to express their opinion on proficiency in FL and 5minutes interview for teachers to express their ideas live on the probable constraints in speaking French language fluently. Then, the data collected by means of the interview and the questionnaires were analysed. The results of the study indicated that school, environmental condition, educational facilities and training of teachers in the field have significant influence on the proficient use of French Language.